Pengaruh Media Smart Explosion Box pada Hasil Belajar Pendidikan Pancasila Siswa Sekolah Dasar - Victorya, Eka Kartika; Arsil, Arsil; Destrinelli, Destrinelli (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2024)
This study aims to explore the effect of using Smart Explosion Box media on student learning outcomes in Pancasila Education subjects in grade IV Elementary School. This study adopted a quantitative approach. The quantitative approach involves data collection, data analysis, and numerical presentation of results. The research was conducted at SDN 182/I Hutan Lindung with the hope of making a positive contribution to the learning outcomes of Pancasila Education in grade IV elementary schools. Based on data analysis by testing the normality and homogeneity of distribution, the average Post-test result in the experimental class reached 75.26, followed by a t test which showed a Sig. (2-tailed) value of 0.000, which is smaller than 0.05. This finding confirms that the use of smart explosion box media significantly affects student learning outcomes in Pancasila education subjects in grade IV elementary schools.